Pengaruh Kerusakan Mechanical Seal terhadap Kinerja Hidraulik Steering Gear di Kapal AHTS Logindo Stamina - Ibnu Septian, Wahyu; Antonius Edy Kristiyono; Prima Yudha Yudianto; Agus Prawoto; Wulan Marlia Sandi (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The steering gear is a vital component in ship operations, functioning to control the ship’s direction accurately. The reliability of this system highly depends on the performance of the hydraulic system, where the mechanical seal plays a key role in maintaining system pressure and preventing oil leakage. This study aims to identify the main factors causing mechanical seal damage and analyze its impact on the performance efficiency of the steering gear AHTS Logindo Stamina. Qualitative data were obtained through participatory observation and in-depth interviews with the second engineer. Meanwhile, quantitative data were gathered by measuring technical parameters such as oil pressure, operating temperature, and rudder movement time, which were then compared with SOLAS standards. This damage results in oil leakage through the mechanical seal gap, abnormal noise in the hydraulic system, and a significant decrease in working pressure of -25,86%. The operational impacts include the occurrence of steering gear failure alarms, decreased hydraulic efficiency of 25.87%, and the risk of system failure that could endanger ship maneuverability. This study recommends preventive maintenance through oil quality monitoring, environmental condition control in the steering gear room, and periodic mechanical seal replacement in accordance with operational standards to maintaining optimal steering system performance.